Transfer of Ultra-Thin Semi-Conductor Films onto Flexible Substrates. (24th August 2016) - Montméat, Pierre; De Nigris Brandolisi, Isadora; Tardif, Samuel; Enot, Thierry; Enyedi, Gregory; Kachtouli, Riadh; Besson, Pascal; Rieutord, François; Fournel, Frank
Abstract : This study describes a process for transferring a 200 nm Si thin film from a SOI onto a flexible substrate. The objective is to find a way for applying a tensile strain onto a very thin semi-conductor film for tensile strain engineering. The processs is achieved with 200 mm wafers and based on a polymer temporary bonding process. Grinding and etching are used for removing the SOI backside substrate and buried oxide. The process leads to a 200 mm Si thin film transferred onto a dicing tape. No crack or ondulation is observed on the film and further tensile strain experiments can be conducted on the structure.